MENINGKATKAN KETERAMPILAN PENGEMBANGAN BAHAN AJAR BERUPA HANDOUT OLEH GURU DI SMP MUHAMMADIYAH 1 PADANG - Zikra Zikra; Febri Yanti (Universitas PGRI Sumatera Barat, 2021)
Learning at SMP Muhammadiyah 1 Padang has not achieved the expected results, this can be seen from the scores of students who are still much below the KKM. One of the causes is the lack of students' understanding of the learning material. For this reason, teacher skills are needed in developing teaching materials so that students can understand the material well. To overcome these problems, it is necessary to hold Community Partnership Program (PKM) activities by guiding and providing training to teachers of SMP Muhammadiyah 1 Padang designing handouts on the subjects they forgive.